Case Study of Reduce Violence in Transient for Capacitor Bank in PEA Distribution System - โสดาบัน, ฉลอง; ชัยสงคราม, วิทยา; ปิยรัตน์, เวคิน (Frontiers in Engineering Innovation Research, 2010)
This paper presents a study of the analysis high fault transient while remove capacitors from a distribution system of 22 kV and 33 kV. In order to investigate and solve this problem, The power circuit topology is modeled by using ATP/EMTP software. The objective of this investigation is to construct the modeling for reducing a high fault during capacitors connected in the distribution system. The result shows that it can implement safety to product workers. Finally, It was able to reduce the cost and it is not necessary to import the equipment products from outsources.